Ultrathin polyimide diaphragm and preparation method thereof
By combining the block polymer template method with click reaction, a uniform mesoporous structure is introduced into the polyimide battery separator, solving the problem of large pore size and uneven distribution of the existing separator and improving the safety and service life of the battery.
Patent Information
- Application Number
- CN202411762738.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
AI Technical Summary
The pore size of existing polyimide battery separators is large and unevenly distributed, which leads to the problem of lithium dendrites piercing the separator, affecting the safety and service life of the battery.
Using the method of combining block polymer template method with click reaction, a uniform mesoporous structure is introduced into the polyimide separator, and an ultra-thin polyimide separator is prepared by photocrosslinking technology.
The uniform transmission of lithium ions in the separator is achieved, the growth of lithium dendrites is inhibited, the safety and service life of the battery are improved, and the pollution and energy consumption in the preparation process are reduced.
Smart Images

Figure CN119560726A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery separator materials, and in particular relates to an ultra-thin polyimide separator and a preparation method thereof. Background Art
[0002] High ionic conductivity and interface-friendly separators are important guarantees for the long life of lithium-ion batteries, and the pore structure of the separator is a key factor affecting the safety and service life of lithium-ion batteries. Currently commercial polyolefin separators have poor heat resistance and pose safety risks.
[0003] Polyimide separators have good heat resistance and have become a very promising polyolefin replacement material. At present, the preparation methods of polyimide battery separators include electrospinning, phase inversion, inorganic filler method, etc. However, the addition of inorganic fillers and pore formers makes the post-processing process cumbersome and easy to pollute the environment. The pore size of the prepared separator is large and unevenly distributed; the polyimide separator prepared by electrospinning has large pores and cannot be precisely controlled; the polyimide prepared by phase inversion has high production efficiency, but it often has the problem of uneven pore size distribution and cannot meet the use requirements of lithium batteries.
[0004] In addition, in the application of diaphragm materials in batteries, the film thickness of the diaphragm is usually thinned to speed up the transport of lithium ions, but at the same time, the thinning of the film thickness will challenge the mechanical stability and pore structure integrity of the diaphragm. Document 1 "Simultaneously blocking chemical crosstalk and internal short circuit via gel-stretching derived nanoporous non-shrinkage separator for safe lithium-ion batteries, Adv. Mater. 34 (2022) 2106335" discloses a PI film with a film thickness of 16 μm and a pore size of 46.7 nm manufactured by a gel stretching orientation method, which effectively prevents chemical crosstalk and internal short circuits and improves the safety of the diaphragm. Document 2 "Porous, robust, thermally stable, and flame retardant nanocellulose / polyimideseparators for safe lithium-ion batteries, J. Mater. Chem. A. 11 (2023) 23360–23369" discloses that a composite PI separator with a film thickness of 10 μm, a pore size of 20 nm and excellent mechanical properties is prepared by introducing decabromodiphenylethane and cellulose nanofibers into PI, but the uniformity of the pore structure of the above two needs to be controlled. In summary, there is an urgent need to develop a polyimide separator that is as thin as possible, has high mechanical strength and a uniform pore structure. Summary of the invention
[0005] In order to overcome the problem that the pore size of the polyimide battery separator prepared by the prior art is large and unevenly distributed, and lithium dendrites are prone to piercing the separator, and to improve battery safety and extend the service life of the battery, the present invention aims to provide an ultra-thin polyimide battery separator and a preparation method thereof, which combines the block polymer template method with the click reaction to gently and efficiently introduce a uniform mesoporous structure into the polyimide separator, thereby fundamentally unblocking the lithium ion transport channel and effectively inhibiting the growth of interfacial lithium dendrites.
[0006] According to a first aspect of the present invention, the present invention first provides a method for preparing an ultra-thin polyimide membrane, comprising the following steps:
[0007] (1) stirring an aromatic diamine and an aromatic dianhydride to carry out a polycondensation reaction, and obtaining an ether-containing polyamic acid after precipitation and drying;
[0008] (2) preparing an amphiphilic block polymer by anionic polymerization or free radical polymerization, so that the molecular weight distribution of the amphiphilic block polymer is no more than 1.1, and the amphiphilic block polymer comprises an etchable hydrophobic block and a cross-linkable hydrophilic block;
[0009] (3) adding the ether-containing polyamic acid, the amphiphilic block polymer, the thiol compound and the photolatent base catalyst to a polar aprotic solvent, and stirring to obtain a mixed solution;
[0010] (4) Photocrosslinking: Spin-coat the mixed solution onto a substrate, remove the solvent, and then irradiate with ultraviolet light. Repeat the spin coating process several times to obtain the result.
[0011] According to one embodiment of the present invention, the polycondensation reaction preparation process in step (1) is as follows: aromatic diamine and aromatic dianhydride are mixed and stirred continuously for 3 hours in an ice bath so that the solution viscosity is 0.4-0.5 dL / g, and the ether-containing polyamic acid is obtained by water precipitation, filtration and vacuum drying.
[0012] According to one embodiment of the present invention, the molar ratio of the aromatic diamine to the aromatic dianhydride in step (1) is 1:1; wherein the aromatic diamine is one or more of 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-diaminodiphenyl ether, 1,3,5-tri(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene; and the aromatic dianhydride is one or more of pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, and 4,4'-phenylenedioxydiphthalic anhydride.
[0013] According to one embodiment of the present invention, the etchable hydrophobic block in step (2) is any one of polystyrene, polymethylstyrene, polyisoprene, and poly(2-vinylpyridine); the cross-linkable hydrophilic block is any one of polyethylene oxide and poly(glycidyl methacrylate); and the block ratio of the two blocks of the block polymer is (0.7 to 0.3): (0.3 to 0.7).
[0014] According to one embodiment of the present invention, the thiol compound in step (3) is a compound having a dithiol or trithiol terminal group; any one of bis(3-mercaptopropionic acid)ethylene glycol, trimethylolpropane-tris(3-mercaptopropionic acid), and pentaerythritol tetrakis(3-mercaptopropionic acid)ester.
[0015] According to one embodiment of the present invention, in step (3), the mass ratio of the polyamic acid: the amphiphilic block polymer: the thiol compound is (0.3-0.5): (0.55-0.3): (0.15-0.2), and the polar aprotic solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran.
[0016] According to one embodiment of the present invention, the photocrosslinking process in step (4) is as follows: spin coating the mixed solution on the surface of the acid-treated silicon wafer at room temperature, keeping it warm at 50-70°C for 1.5 hours to remove the solvent, and then irradiating it with ultraviolet light for 3-5 minutes, heating it to 280-350°C at a rate of 1-3°C / min and keeping it warm for 1 hour, and repeating the spin coating multiple times.
[0017] According to one embodiment of the present invention, the photolatent base catalyst is one of 1,5-diazabicyclo[4.3.0]non-5-ene, 5-(2'-nitrobenzyl)-1,5-diazabicyclo[4.3.0]nonane and 5-(2'-nitrobenzyl)-1,5-diazabicyclo[4.3.0]nonane.
[0018] According to another aspect of the present invention, the present invention further provides an ultra-thin polyimide membrane prepared by the above method, wherein the thickness of the ultra-thin polyimide membrane is 6 to 50 μm.
[0019] According to another aspect of the present invention, the present invention also provides use of the polyimide separator in a lithium ion battery.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The preparation method of the present invention combines the block polymer template method with the click reaction method, thereby gently and efficiently introducing a uniform mesoporous structure into the polyimide separator, which can greatly improve the transmission capacity of lithium ions in the separator.
[0022] (2) The preparation process of the present invention is gentle, efficient, pollution-free, and environmentally friendly. The click reaction method is carried out under low temperature conditions and can well control the collapse of the mesoporous structure during heat treatment, providing a certain theoretical basis for the subsequent 3D printing technology to prepare ultrathin polyimide membranes.
[0023] (3) The polyimide separator prepared by the present invention contains a rigid aromatic ring structure and a flexible ether bond, has good flexibility and interface compatibility, is conducive to the assembly of practical lithium batteries, is thin and has a small mesopore size, is conducive to the uniform deposition of lithium ions and inhibits the growth of lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an optical photograph of the ultrathin polyimide membrane prepared in Example 1.
[0025] Figure 2 This is a scanning electron microscope image of the ultrathin polyimide membrane prepared in Example 1.
[0026] Figure 3This is an atomic force microscope image of the ultrathin polyimide membrane prepared in Example 3.
[0027] Figure 4 This is an atomic force microscope image of the ultrathin polyamic acid membrane prepared in Comparative Example 1.
[0028] Figure 5 This is an atomic force microscope image of the ultrathin polyimide membrane prepared in Comparative Example 2. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0030] The present invention provides a method for preparing an ultrathin polyimide diaphragm, comprising the following steps:
[0031] (1) stirring an aromatic diamine and an aromatic dianhydride to carry out a polycondensation reaction, and obtaining an ether-containing polyamic acid after precipitation and drying;
[0032] (2) preparing an amphiphilic block polymer by anionic polymerization or free radical polymerization, so that the molecular weight distribution of the amphiphilic block polymer is no more than 1.1, and the amphiphilic block polymer comprises an etchable hydrophobic block and a cross-linkable hydrophilic block;
[0033] (3) adding the ether-containing polyamic acid, the amphiphilic block polymer, the thiol compound and the photolatent base catalyst to a polar aprotic solvent, and stirring to obtain a mixed solution;
[0034] (4) Photocrosslinking: Spin-coat the mixed solution onto a substrate, remove the solvent, and then irradiate with ultraviolet light. Repeat the spin coating process several times to obtain the result.
[0035] In some embodiments, the thickness of each spin coating is 30-100 nm.
[0036] In some embodiments, the polycondensation reaction preparation process of step (1) is as follows: aromatic diamine and aromatic dianhydride are mixed and stirred continuously for 3 hours in an ice bath to make the solution viscosity 0.4-0.5 dL / g, and then precipitated with water, filtered and vacuum dried to obtain the ether-containing polyamic acid.
[0037] In some embodiments, the molar ratio of the aromatic diamine to the aromatic dianhydride in step (1) is 1:1; wherein the aromatic diamine is one or more of 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-diaminodiphenyl ether, 1,3,5-tri(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene; and the aromatic dianhydride is one or more of pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, and 4,4'-dioxydiphthalic anhydride.
[0038] In some embodiments, the etchable hydrophobic block in step (2) is any one of polystyrene, polymethylstyrene, polyisoprene, and poly(2-vinylpyridine); the cross-linkable hydrophilic block is any one of polyethylene oxide and poly(glycidyl methacrylate); and the block ratio of the two blocks of the block polymer is (0.7 to 0.3): (0.3 to 0.7).
[0039] In some embodiments, the thiol compound of step (3) has a dithiol or trithiol terminal group; any one of bis(3-mercaptopropionic acid)ethylene glycol, trimethylolpropane-tris(3-mercaptopropionic acid), and pentaerythritol tetrakis(3-mercaptopropionic acid)ester.
[0040] In some embodiments, the mass ratio of the polyamic acid in step (3): the amphiphilic block polymer: the thiol compound is (0.3-0.5): (0.55-0.3): (0.15-0.2), and the polar aprotic solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran.
[0041] In some embodiments, the photocrosslinking process in step (4) is as follows: spin coating the mixed solution on the surface of the acid-treated silicon wafer at room temperature, keeping it warm at 50-70°C for 1.5 hours to remove the solvent, and then irradiating it with ultraviolet light for 3-5 minutes, heating it to 280-350°C at a rate of 1-3°C / min and keeping it warm for 1 hour, and repeating the spin coating multiple times.
[0042] In some embodiments, the photolatent base catalyst is one of 1,5-diazabicyclo[4.3.0]non-5-ene, 5-(2'-nitrobenzyl)-1,5-diazabicyclo[4.3.0]nonane, and 5-(2'-nitrobenzyl)-1,5-diazabicyclo[4.3.0]nonane.
[0043] The following are specific embodiments:
[0044] Example 1
[0045] A method for preparing a high temperature resistant polyimide diaphragm and a carbonized film is prepared by the following preparation steps:
[0046] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3-4 hours to obtain a precursor solution with a viscosity of 0.4-0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;
[0047] 2) Polystyrene (PS) and poly(glycidyl methacrylate) (PGMA) are polymerized by anionic polymerization to obtain BCP (PS-b-PGMA, 60:40 wt%) having a number average molecular weight of 60,000 to 80,000 and a molecular weight distribution (PDI) of 1.1;
[0048] 3) 0.04g of precursor powder, 0.03g of BCP, 0.03g of bis(3-mercaptopropionic acid)ethylene glycol and 2wt% of the photolatent base catalyst 1,5-diazabicyclo[4.3.0]non-5-ene were dissolved in 15ml of N,N-dimethylacetamide and stirred at room temperature to obtain a uniform mixed solution. The mixed solution was spin-coated on a silicon wafer treated with sulfuric acid, and then the glass plate was placed in an oven at 60°C for 1.5h, followed by UV irradiation for 3min, and finally heated to 350°C at a rate of 3°C / min and kept warm for 1h. Spin-coating was performed on 50-80nm each time, and the spin coating was repeated several times. The optical photograph and scanning electron microscope image of the obtained ultrathin polyimide membrane are shown in the following figure. Figure 1 and Figure 2 As shown, the existence of uniform mesoporous structure is proved. The thickness of the polyimide battery separator is 10 μm.
[0049] Example 2
[0050] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3-4 hours to obtain a precursor solution with a viscosity of 0.4-0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;
[0051] 2) Polystyrene (PS) and poly(glycidyl methacrylate) (PGMA) are polymerized by anionic polymerization to obtain BCP (PS-b-PGMA, 60:40 wt%) having a number average molecular weight of 60,000 to 80,000 and a molecular weight distribution (PDI) of 1.08;
[0052] 3) 0.05g of precursor powder, 0.03g of BCP, 0.02g of trimethylolpropane-tris(3-mercaptopropionate) and 2wt% of photolatent base catalyst 1,5-diazabicyclo[4.3.0]non-5-ene were dissolved in 5ml of N,N-dimethylacetamide, and stirred at room temperature to obtain a uniform mixed solution. The mixed solution was spin-coated on a silicon wafer treated with sulfuric acid, and then the glass plate was placed in an oven at 60°C for 1.5h, then UV-irradiated for 5min, and the mixed solution was spin-coated on the coated silicon wafer multiple times, and kept warm in an oven at 80°C for 0.5h, then UV-irradiated for 3-5min, and finally heated to 350°C at a rate of 5°C / min and kept warm for 1h, and 80-100nm was spin-coated each time, and the spin coating was repeated multiple times. The thickness of the polyimide battery separator is 50μm.
[0053] Example 3
[0054] 1) dissolving 1,3-bis(3-aminophenoxy)benzene and 4,4'-dioxyphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3-4 hours to obtain a precursor solution with a viscosity of 0.4-0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;
[0055] 2) Polystyrene (PS) and poly(glycidyl methacrylate) (PGMA) are polymerized by anionic polymerization to obtain BCP (PS-b-PGMA, 60:40 wt%) having a number average molecular weight of 60,000 to 80,000 and a molecular weight distribution (PDI) of 1.08;
[0056] 3) 0.04g of precursor powder, 0.04g of BCP, 0.02g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 2wt% of the photolatent base catalyst 1,5-diazabicyclo[4.3.0]non-5-ene were dissolved in 5ml of N,N-dimethylacetamide and stirred at room temperature to obtain a uniform mixed solution. The mixed solution was spin-coated on a silicon wafer treated with sulfuric acid, and then the glass plate was placed in an oven at 60°C for 1.5h, followed by ultraviolet irradiation for 3min, and finally heated to 350°C at a rate of 5°C / min and kept warm for 1h. Spin-coating was performed at 50-80nm each time, and the spin coating was repeated several times. The polyimide battery separator has a thickness of 6μm, and its atomic force microscope image is shown in the figure. Figure 3 As shown, the existence of uniform mesoporous structure is demonstrated.
[0057] Example 4
[0058] 1) dissolving 1,3-bis(3-aminophenoxy)benzene and 4,4'-dioxyphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3-4 hours to obtain a precursor solution with a viscosity of 0.4-0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;
[0059] 2) Polystyrene (PS) and poly(glycidyl methacrylate) (PGMA) are polymerized by anionic polymerization to obtain BCP (PS-b-PGMA, 70:30 wt%) having a number average molecular weight of 60,000 to 80,000 and a molecular weight distribution (PDI) of 1.05;
[0060] 3) 0.05g of precursor powder, 0.03g of BCP, 0.02g of tetrakis(3-mercaptopropionic acid) pentaerythritol ester and 2wt% of the photolatent base catalyst 1,5-diazabicyclo[4.3.0]non-5-ene were dissolved in 5ml of N,N-dimethylacetamide and stirred at room temperature to obtain a uniform mixed solution. The mixed solution was spin-coated on a silicon wafer treated with sulfuric acid, and then the glass plate was placed in an oven at 60°C for 1.5h, then UV-irradiated for 3min, and finally heated to 350°C at a rate of 5°C / min and kept warm for 1h, and 80-100nm was spin-coated each time, and the spin coating was repeated multiple times. The thickness of the polyimide battery separator is 16μm.
[0061] Comparative Example 1
[0062] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3-4 hours to obtain a precursor solution with a viscosity of 0.4-0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;
[0063] 2) Polystyrene (PS) and poly(glycidyl methacrylate) (PGMA) are polymerized by anionic polymerization to obtain BCP (PS-b-PGMA, 80:20 wt%) having a number average molecular weight of 60,000 to 80,000 and a molecular weight distribution (PDI) of 1.2;
[0064] 3) 0.04g of precursor powder, 0.03g of BCP, 0.03g of bis(3-mercaptopropionic acid)ethylene glycol and 2wt% of the photolatent base catalyst 1,5-diazabicyclo[4.3.0]non-5-ene were dissolved in 15ml of N,N-dimethylacetamide and stirred at room temperature to obtain a uniform mixed solution. The mixed solution was spin-coated on a silicon wafer treated with sulfuric acid, and then the glass plate was placed in an oven at 60°C for 1.5h. The atomic force microscope image is shown in the figure. Figure 4 As shown, the existence of a macroscopic phase separation microstructure can be seen.
[0065] Then, the film was irradiated with ultraviolet light for 3 minutes, and finally the temperature was raised to 350°C at a rate of 3°C / min and kept at that temperature for 1 hour, and 50-80nm was spin-coated each time, and the spin-coating was repeated for multiple times to obtain the polyimide battery separator with a thickness of 40 μm.
[0066] Comparative Example 2
[0067] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3-4 hours to obtain a precursor solution with a viscosity of 0.4-0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;
[0068] 2) Polystyrene (PS) and poly(glycidyl methacrylate) (PGMA) are polymerized by anionic polymerization to obtain BCP (PS-b-PGMA, 60:40 wt%) having a number average molecular weight of 60,000 to 80,000 and a molecular weight distribution (PDI) of 1.08;
[0069] 3) 0.05g of precursor powder, 0.04g of BCP, 0.01g of bis(3-mercaptopropionic acid)ethylene glycol and 2wt% of the photolatent base catalyst 1,5-diazabicyclo[4.3.0]non-5-ene were dissolved in 15ml of N,N-dimethylacetamide and stirred at room temperature to obtain a uniform mixed solution. The mixed solution was spin-coated on a silicon wafer treated with sulfuric acid, and then the glass plate was placed in an oven at 60°C for 1.5h, followed by ultraviolet irradiation for 3min, and finally heated to 350°C at a rate of 3°C / min and kept warm for 1h. Spin-coating was performed on 50-80nm each time, and the spin coating was repeated several times. The thickness of the polyimide battery separator is 36μm. Its atomic force microscope image is shown as follows Figure 5 As shown, only a partial mesoporous structure can be seen.
[0070] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultrathin polyimide diaphragm, characterized in that: The following steps are involved: (1) stirring an aromatic diamine and an aromatic dianhydride to carry out a polycondensation reaction, and obtaining an ether-containing polyamic acid after precipitation and drying; (2) preparing an amphiphilic block polymer by anionic polymerization or free radical polymerization, so that the molecular weight distribution of the amphiphilic block polymer is no more than 1.1, and the amphiphilic block polymer comprises an etchable hydrophobic block and a cross-linkable hydrophilic block; (3) adding the ether-containing polyamic acid, the amphiphilic block polymer, the thiol compound and the photolatent base catalyst to a polar aprotic solvent, and stirring to obtain a mixed solution; (4) Photocrosslinking: Spin-coat the mixed solution onto a substrate, remove the solvent, and then irradiate with ultraviolet light. Repeat the spin coating process several times to obtain the result.
2. The method for producing an ultra-thin polyimide membrane according to claim 1, characterized in that: The polycondensation reaction preparation process of step (1) is as follows: aromatic diamine and aromatic dianhydride are mixed and stirred continuously for 3 hours in an ice bath to make the solution viscosity 0.4-0.5 dL / g, and then the solution is precipitated with water, filtered and vacuum dried to obtain the ether-containing polyamic acid.
3. The method for producing an ultra-thin polyimide membrane according to claim 1, characterized in that: The molar ratio of the aromatic diamine to the aromatic dianhydride in step (1) is 1:1; wherein the aromatic diamine is one or more of 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-diaminodiphenyl ether, 1,3,5-tri(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene; and the aromatic dianhydride is one or more of pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, and 4,4'-phenylenedioxydiphthalic anhydride.
4. The method for producing an ultra-thin polyimide membrane according to claim 1, characterized in that: The etchable hydrophobic block in step (2) is any one of polystyrene, polymethylstyrene, polyisoprene, and poly(2-vinylpyridine); the cross-linkable hydrophilic block is any one of polyethylene oxide and poly(glycidyl methacrylate); and the block ratio of the two blocks of the block polymer is (0.7-0.3):(0.3-0.7).
5. The method for producing an ultra-thin polyimide membrane according to claim 1, characterized in that: The thiol compound of step (3) has a dithiol or trithiol terminal group; any one of bis(3-mercaptopropionic acid)ethylene glycol, trimethylolpropane-tris(3-mercaptopropionic acid ester), and pentaerythritol tetrakis(3-mercaptopropionic acid) ester.
6. The method for producing an ultra-thin polyimide membrane according to claim 1, characterized in that: In step (3), the mass ratio of the polyamic acid: the amphiphilic block polymer: the thiol compound is (0.3-0.5): (0.55-0.3): (0.15-0.2), and the polar aprotic solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran.
7. The method for producing an ultra-thin polyimide membrane according to claim 1, characterized in that: The photocrosslinking process in step (4) is as follows: spin coating the mixed solution on the surface of the acid-treated silicon wafer at room temperature, then heating to 50-70°C and keeping it warm for 1.5 hours to remove the solvent, and then irradiating with ultraviolet light for 3-5 minutes, heating to 280-350°C at a rate of 1-3°C / min and keeping it warm for 1 hour, and repeating the spin coating multiple times.
8. The method for producing an ultra-thin polyimide membrane according to claim 1, characterized in that: The photolatent base catalyst is one of 1,5-diazabicyclo[4.3.0]non-5-ene, 5-(2'-nitrobenzyl)-1,5-diazabicyclo[4.3.0]nonane and 5-(2'-nitrobenzyl)-1,5-diazabicyclo[4.3.0]nonane.
9. An ultra-thin polyimide membrane according to any one of claims 1 to 8, characterized in that: The thickness of the ultra-thin polyimide membrane is 6-50 μm.
10. Use of the ultra-thin polyimide separator according to claim 9 in a lithium battery.